Effects of the amino acid mixture, ‘NutriMix’, on growth performance, non-specific immunity and intestinal health in sea cucumber (Apostichopus japonicus) - Jiali Wu; Chengjie Lv; Xiaojing Lv; Yongliang Liu; Weiwei Zhang; Dinglong Yang; Jianmin Zhao (Comparative Immunology Reports)
In the present study, a mixture of amino acids (NutriMix) was used to evaluate its effects on growth performance, non-specific immunity and intestinal health in sea cucumber (Apostichopus japonicus). During a 56-day feeding trial, the sea cucumber (0.92 ± 0.05g ) was fed with basal diet (control, CT) and treatment diets supplemented at different doses of amino acid mixture, 0.5 ‰ (AL), 1 ‰ (AM) and 2 ‰ (AH) (w/w, parts per thousand). The weight gain rate (WGR) and specific growth rate (SGR) of A. japonicus fed amino acid mixture were significantly increased in the AM group (P < 0.05). Additionally, the trypsin and lipase activities of the intestine were significantly increased in the AM group (P < 0.05). Analysis of the intestinal morphological features indicated that in the AM group, the intestinal structure of sea cucumber was more regular, longer, with intact intestinal villi, and with a complete muscular layer. Also, the muscle and mucosal layers are thicker. Alpha diversity analysis showed that the amino acid mixture-supplemented groups had higher intestinal microbial richness and diversity than the CT group. Furthermore, beta diversity analysis demonstrated distinct bacterial community structures between the amino acid mixture-supplemented groups and the control group, with Proteobacteria, Bacteroidota, and Verrucomicrobiota being the most abundant phyla. Notably, the AM group exhibited significant differences in intestinal microbiota composition, which may play a crucial role in the improved growth performance and health of A. japonicus. In conclusion, dietary addition of amino acid mixture could effectively promote the growth of A. japonicus, achieve cost-sparing effect in aquafeed, improve its digestion and immunity capacity to a certain extent, and actively regulate the intestinal microflora of A. japonicus.